(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
The aim of the research was to know the plant species which used as a natural colorant and its exploiting traditionally by Tribe of Marori Men-Gey. This Research was executed at area of Wasur National Park in Merauke regency. Method used was descriptive method with the direct observation technique in field. Result of research indicate that the natural colorant plant exploited by tribe of Marori Men-Gey as much 7 species included in 6 family that was Vaccinium sp. (Cacinaceae), Morinda citrifolia L. (Rubiaceae), Curcuma domestica Val. (Zingiberaceae), Mangifera indica L. (Anacardiaceae), Ziziplus sp. (Myrtaceae), Gmelina sp. (Verbenaceae) and Zyzygium sp (Myrtaceae). Part of plant exploited cover the root, rhizome, bark, rubber, leaf and fruit. From 7 the colorant plant species, 4 species yielding color yellow that was Vaccinium sp., C. domestica, M. citrifolia and M. indica, 2 species yield the riddling that was Ziziplus sp. and Gmelina sp. and also 1 species yielding black color that was Zyzygium sp. Colorant plant exploited by tribe of Marori Men-Gey as traditional equipments colorant, food colorant and body colorantÂ Key words: natural colourant plant, Marori Men-Gey trible, Wasur National Park, Merauke.